Nanomolar Synthesis in Droplet Microarrays with UV‐Triggered On‐Chip Cell Screening. Issue 10 (27th January 2020) - Brehm, Marius; Heissler, Stefan; Afonin, Sergii; Levkin, Pavel A.
Abstract: Miniaturization and parallelization of combinatorial organic synthesis is important to accelerate the process of drug discovery while reducing the consumption of reagents and solvents. This work presents a miniaturized platform for on‐chip solid‐phase combinatorial library synthesis with UV‐triggered on‐chip cell screening. The platform is based on a nanoporous polymer coating on a glass slide, which is modified via photolithography to yield arrays of hydrophilic (HL) spots surrounded by superhydrophobic (SH) surface. The combination of HL spots and SH background enables confinement of nanoliter droplets, functioning as miniaturized reactors for the solid‐phase synthesis. The polymer serves as support for nanomolar solid‐phase synthesis, while a photocleavable linker enables the release of the synthesized compounds into the droplets containing live cells. A 588 compound library of bisamides is synthesized via a four‐component Ugi reaction on the chip and products are detected via stamping of the droplet array onto a conductive substrate and subsequent matrix‐assisted laser desorption ionization mass spectrometry. The light‐induced cleavage shows high flexibility in screening conditions by spatial, temporal, and quantitative control. Abstract : A platform for parallel nanomolar solid‐phase combinatorial synthesis is demonstrated with possible subsequent on‐chip cell screening. The phototriggered release offers spatial, temporal, and quantitative control of compound release into distinct droplets and allows high variability in the screening conditions. Microscopic readout is possible due to the transparency of the substrate.